Coffee Drinking and Liver Enzyme Levels with Gallbladder Hormone Activity: Konsumsi Kopi dan Tingkat Enzim Hati dengan Aktivitas Hormon Kandung Empedu - Kadhum, Hanaa Salman; Alessa, Ahmed Hatem Ahmed; Abdulqader, Marwa Jasim (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Coffee is among the most consumed beverages worldwide, with reported benefits and risks on metabolic and hepatobiliary health. Specific Background: Previous research has suggested protective roles of coffee against liver disease and gallstone formation, yet contradictory evidence highlights possible adverse enzymatic changes. Knowledge Gap: Limited studies have simultaneously examined the effects of coffee on both liver enzyme activity and gallbladder hormone secretion in habitual coffee consumers. Aims: This study aimed to evaluate the impact of regular coffee consumption on liver enzymes (ALT, AST, ALP, bilirubin) and the gallbladder hormone cholecystokinin (CCK). Results: Among 32 participants, coffee intake was associated with significant increases in ALP and AST levels (p<0.05), particularly in males and individuals over 25 years, while ALT, bilirubin, and CCK largely remained within normal ranges. Novelty: The study provides integrated evidence that excessive coffee consumption (>2 cups/day) may simultaneously alter hepatic enzyme profiles and modulate gallbladder hormonal response. Implications: These findings underscore the need for cautious monitoring of liver health in heavy coffee drinkers and highlight the dual metabolic effects of coffee, suggesting that moderate intake may balance its hepatoprotective potential with risks of enzyme elevation.Highlight : Coffee consumption is linked to increased ALP and AST levels. Age and gender influence the degree of liver enzyme changes. Coffee stimulates CCK, affecting gallbladder function. Keywords : Coffee Drinking, Liver Enzymes, Gallbladder, Cholecystokinin, Health Effects